2019
DOI: 10.1590/1414-431x20187637
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of insulin administration on liver glucose metabolism in strength-trained healthy mice

Abstract: Non-diabetic individuals use hormones like insulin to improve muscle strength and performance. However, as insulin also leads the liver and the adipose tissue to an anabolic state, the purpose of this study was to investigate the effects of insulin on liver metabolism in trained non-diabetic Swiss mice. The mice were divided into four groups: sedentary treated with saline (SS) or insulin (SI) and trained treated with saline (TS) or insulin (TI). Training was made in a vertical stair, at 90% of the maximum load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Previous results from our research group using this same experimental model showed that there was a significant difference in relation to body weight, where trained animals (TS and TI) had less weight when compared to sedentary groups. Biochemical data showed that the use of insulin increased the dosage of hepatic glycogen and the release of basal glucose from the liver, and its use associated with training meant that the increase in exercise-induced gluconeogenesis was reduced (Pereira, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results from our research group using this same experimental model showed that there was a significant difference in relation to body weight, where trained animals (TS and TI) had less weight when compared to sedentary groups. Biochemical data showed that the use of insulin increased the dosage of hepatic glycogen and the release of basal glucose from the liver, and its use associated with training meant that the increase in exercise-induced gluconeogenesis was reduced (Pereira, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Each week a new ML test was performed, but starting from the ML of the previous week, to adjust the training intensity. Mice from groups SS and SI were subjected to the ML test on the first and last week of the experimental period (Pereira, et al, 2019).…”
Section: Resistance Training Modelmentioning
confidence: 99%
“…The trained groups were scheduled sequentially, so that no more than 10 mice were under training during a given period. The apparatus used for familiarization, training and maximal load (ML) tests, as well as the training protocol (load, frequency, format of the sessions and periods of training) were adapted from previous studies (Cassilhas et al, 2013;Muller et al, 2019;Neto et al, 2016;Pereira et al, 2019).…”
Section: R a F Tmentioning
confidence: 99%
“…The training with vertical ladder and overload presents many advantages: easy handling and low cost; control of the training load; individualized training intensity; less discomfort and distress to the animal; the desired physiological response (that is, increased blood lactate levels) achieved easily and in shorter training sessions; and it can be used for continuous (Pereira et al, 2019) or interval (Muller et al, 2019) training formats.…”
Section: R a F Tmentioning
confidence: 99%